2020
DOI: 10.1111/jocs.14522
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prealbumin does not impact outcomes after left ventricular assist device implantation

Abstract: Background: This single-center, the retrospective study evaluates the impact of preoperative serum prealbumin levels on outcomes after left ventricular assist device (LVAD) implantation.Methods: Adults undergoing LVAD implantation, with a recorded preoperative prealbumin level, between 2004 to 2018 were included. Primary outcomes included rates of 1-year survival and secondary outcomes included rates of postimplant adverse events. Threshold regression and restricted cubic splines were utilized to identify a cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hs-CRP can be used to effectively assess the inflammatory response in vivo and the severity of AMI, and it is closely related to the morbidity and mortality rates of cardiovascular events [12] . Besides, PAB is an acute phase reactive protein able to not only effectively evaluate the synthetic ability of the liver, but also reflect the severity of inflammatory response in patients with cardiovascular disease [13] . Matsunaga et al [14] found that the content of PAB in the peripheral blood of patients with unstable angina pectoris is far lower than that in normal people.…”
Section: Discussionmentioning
confidence: 99%
“…Hs-CRP can be used to effectively assess the inflammatory response in vivo and the severity of AMI, and it is closely related to the morbidity and mortality rates of cardiovascular events [12] . Besides, PAB is an acute phase reactive protein able to not only effectively evaluate the synthetic ability of the liver, but also reflect the severity of inflammatory response in patients with cardiovascular disease [13] . Matsunaga et al [14] found that the content of PAB in the peripheral blood of patients with unstable angina pectoris is far lower than that in normal people.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nutrition counseling is recommended to guide MNT according to the patients' individual tolerance [17 && ]. However, it must be acknowledged that no specific nutrition screening or assessment tool is recommended in the ISHLT MCS guideline 2023, and that biochemical markers, which are recommended to be used, such as albumin and prealbumin may rather provide information about the patients' inflammatory status than about nutrition status [18,19]. As validated screening and assessment tools to evaluate the nutrition status in patients on MCS are still lacking, a mixture of methods including anthropometric, instrumental, functional, metabolic, and gastrointestinal measures should be implemented in routine clinical practice (Fig.…”
Section: Nutrition Statusmentioning
confidence: 99%
“…Older age and nutritional inadequacy have been associated with worse outcomes following cardiac surgery due to decreased functional reserve and increased likelihood for frailty, falls, infection, and pulmonary complications. [22][23][24][25][26][27] Furthermore, preoperative renal and hepatic dysfunction, as evidenced by elevated creatinine and INR, are robust predictors of increased postoperative morbidity and mortality in adult cardiac surgery. 28 In our study, nearly half of the cohort required massive transfusion during the early perioperative period, which represent a significant portion of the advanced heart failure population undergoing LVAD implantation.…”
Section: Study Findings and Implicationsmentioning
confidence: 99%
“…In our retrospective study, patients who required perioperative massive transfusion exhibited several traditional risk factors for adverse outcomes including older age, male, lower albumin, elevated serum creatinine, and increased INR. Older age and nutritional inadequacy have been associated with worse outcomes following cardiac surgery due to decreased functional reserve and increased likelihood for frailty, falls, infection, and pulmonary complications 22–27 . Furthermore, preoperative renal and hepatic dysfunction, as evidenced by elevated creatinine and INR, are robust predictors of increased postoperative morbidity and mortality in adult cardiac surgery 28 .…”
Section: Commentmentioning
confidence: 99%